Effectiveness of Pleidooi by The Supreme Of Criminal Murder - Muhammad Baharuddin; Akhmad Khisni (Law Development Journal, 2020)
The purpose of this study is to study and analyze the effectiveness of the pleaqs submitted by the accused as the perpetrator of the crime of murder in the trial process. In this research, the writer used sociological juridical method with the research specification in the form of descriptive analysis. The data used for this research are primary and secondary data. Based on the results of the research which concluded that in the analysis of the trial process of the verdict in the murder case with the perpetrator Hamim in accordance with the series of decisions Number: 73 / PID.B / 2015 / PN.Kds, the Judge gave a heavier verdict than the prosecutor's demands by using 2 (Article), each of which causes a different victim, namely the victim who died and was seriously injured in Article 338 of the Criminal Code and Article 351 paragraph (1) of the Criminal Code.